2011
DOI: 10.1007/s11095-011-0539-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvent Composition on the Miscibility and Physical Stability of Naproxen/PVP K 25 Solid Dispersions Prepared by Cosolvent Spray-Drying

Abstract: Spray-drying from a cocktail of good solvent and anti-solvent with narrower volatility difference produces solid dispersions with better miscibility and physical stability resulting from the simultaneous effect on the polymer conformation and better dispersivity of drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 38 publications
6
73
2
Order By: Relevance
“…(4). Physicochemical characteristics of a drug in solid dispersion may be affected by process, process variables, and carrier compositions (13,14). He et al reported that spray freeze drying process provides physically and chemically stable amorphous solid dispersion of baicalein, while the dispersion prepared by solvent evaporation showed recrystallization of the drug (14).…”
Section: Introductionmentioning
confidence: 99%
“…(4). Physicochemical characteristics of a drug in solid dispersion may be affected by process, process variables, and carrier compositions (13,14). He et al reported that spray freeze drying process provides physically and chemically stable amorphous solid dispersion of baicalein, while the dispersion prepared by solvent evaporation showed recrystallization of the drug (14).…”
Section: Introductionmentioning
confidence: 99%
“…This fundamental finding supports our previous hypothesis that melt-homogenized solvent cast films are likely to reflect the intrinsic miscibility of the considered API:excipient in a melt state (26). This hypothesis has recently been verified on Naproxen/PVP K25 solid dispersions (31). …”
Section: Discussionmentioning
confidence: 66%
“…The rate of solvent evaporation will be competing with the rate of solvent diffusion out of the drying droplet due to polymer "skinning" at the surface of the droplet as well as the general viscosity increase during glass formation. Consequently, studies have shown that the spray solvent composition can impact the miscibility and physical stability of spray dried amorphous solid dispersions (Paudel and Van den Mooter 2012). This complexity and its implications on surface composition of the resulting droplet will be discussed in a subsequent section of this chapter.…”
Section: Phase State Implications On Kinetics Of Solventmentioning
confidence: 97%